Clinical supervision experiences of third year nursing students by staff nurses at Mzuzu Central Hospital - Malikha, Evelyn (2021)
Nursing Students require clinical supervision in order to be supported and guided in acquisition of competences and skills for their professional growth. Nursing students at Mzuzu Central Hospital are no exception. Anecdotal report showed that nursing students were not guided by staff nurses during the clinical practice at MCH and this motivated the researcher to do an investigation. Insufficient clinical supervision hampers student professional growth and development, creating clinically incompetent practitioners with harmful percussion for their patient and the profession. The purpose for this study was to explore the experiences of Mzuzu University third year undergraduate nursing students’ clinical supervision during their clinical learning at MCH. Clearance to conduct the study was obtained from COMREC, MCH research committee and from participants’ consent agreement. A qualitative descriptive study was done among the third year undergraduate nursing students during their clinical practices at MCH. Target population was the entire third year undergraduate nursing student (40) doing clinical practice at MCH. Purposive sampling method was used to recruit 13 participants for the study upon reaching data saturation. A semi- structured interview guide was utilized to collect data and analysis was done using themes. Findings reveal that poor student –supervisor relationship, inadequate resources in the placement area, and the growing numbers of students in the placement area contributed to inadequate clinical supervision of nursing students by clinical staff. It was also evident that clinical staffs at MCH were struggling as they were understaffed and some were not competent enough to supervise the students which made things difficult as it was not easy to support students as expected. Therefore, recommendations such as clinical staff orientation in clinical supervision through in service training and supervisor –student ratio as NMCM recommends are made by the researcher to the learning institution as well as the clinical teaching facility.